Tectonic and stratigraphic evolution of the central Exmouth Plateau, NW Shelf of Australia. (February 2022) - Bilal, Awad; McClay, Ken
Abstract: A detailed tectono-stratigraphic analysis of the Mesozoic through Present-day structures and sedimentary sequences has been carried-out on a very large merged 3-D seismic survey that covers the great part of the central Exmouth Plateau, northern Carnarvon Basin, NW Shelf of Australia. Four main megasequences bounded by regional unconformities have been delineated. They are; (1) Megasequence-I - Early-Late Triassic pre-extension, (2) Megasequence-II - Latest Triassic (Rhaetian)-earliest Late Jurassic (Oxfordian) syn-extension; (3) Megasequence-III - Late Jurassic-Early Cretaceous post-extension; and (4) Megasequence-IV - Early Cretaceous-Present-day passive margin strata. Three populations of extensional faults and a previously unrecognised compressional phase of folding have been identified. The main Mesozoic (Rhaetian-Oxfordian) WNW-directed extension produced domino-style planar extensional faults (Fault System 1) with two principle fault sets; (i) large N–S to NNE-SSW-trending, west-dipping faults and (ii) smaller-scale, largely antithetic east-dipping faults. The large faults are possibly reactivated pre-existing deeper and older faults (possibly related to listric growth faults of the large Lower-to Mid-Triassic Mungaroo delta) as well as completely new faults developed in the upper part of the Triassic Mungaroo Formation. Synclinal hangingwall basins of this system are strongly segmented and underfilled with little (<450 m) syn-extensional sedimentation. Fault System 1 was reactivated during the Early Cretaceous-Neogene post-extension stage and strongly influenced the development of the segmented NNE-SSW-trending Fault System 2 in the Cenozoic strata. Two stacked polygonal non-tectonic fault tiers (Fault System 3) separated by little deformed stratigraphy occur within the Berriasian to Pliocene post-extension sequences. In the early post-extension phase, Late Jurassic to Early Cretaceous NNE-SSW-directed minor contraction event produced broad WNW-ESE-striking folds in the Triassic-Early Cretaceous strata. This study documents the development of the extensional fault systems and proposes new 4-D tectono-stratigraphic evolutionary models for the central Exmouth Plateau. The results of this study have wider implications for the tectono-stratigraphy of the northern Carnarvon Basin and future exploration. Highlights: Long-lived, multi-phase extension with local reactivation in the central Exmouth Plateau. Four Triassic to Recent megasequences bounded by regional unconformities define the tectono-stratigraphy of the area. Three populations of extensional faults and a previously unrecognised compressional phase of folding are presented. Two distinctive polygonal fault tiers form pseudo-conjugate arrays with the tectonic faults.. Fault distribution, style, and magnitudes vary temporally and spatially.